Pengaruh Media Pembelajaran, Lingkungan Sekolah Dan Kompetensi Pedagogik Terhadap Motivasi Belajar Siswa - Arman Arman (Universitas Negeri Makassar, 2020)
This study aims to determine (i) the effect of learning media partially on student motivation in SDN 245 Batutompo, Rilau Ale Subdistrict, Bulukumba District (ii) partially influence the school environment on student motivation in SDN 245 Batutompo, Rilau Ale Subdistrict, Bulukumba District (iii) partial influence of pedagogical competence on student motivation in SDN 245 Batutompo, Rilau Ale Subdistrict, Bulukumba District (iv) the influence of learning media, school environment, and pedagogic competence simultaneously on student motivation in SDN 245 Batutompo Subdistrict, Rilau Ale, Bulukumba District. This study uses a quantitative approach that examines the relationship between learning media, the school environment and pedagogical competence on student motivation. Data analysis techniques using quantitative techniques with inferential statistical approaches, namely multiple linear regression analysis. The results showed that simultaneous learning media, school environment, and pedagogical competencies had a positive and significant effect on student motivation in SDN 245 Batutompo, Rilau Ale District, Bulukumba Regency. While the partial test results show that the learning media, school environment and pedagogical competence each have a positive and significant effect on student motivation in SDN 245 Batutompo, Rilau Ale District, Bulukumba Regency.